Mobile communication providers’ corporate brand as a relationship building pillar - Jurisic, Brigita (2009)
The mobile communications industry is an important sector with European total revenues growing approximately 10% per year (GSMA, 2008). Markets all over Europe are mature and the operators engage in intense competition for customers. Heavy investments are made in marketing, through corporate brand enforcement and innovation in development of new products. The aim of this paper is to outline different variables of corporate brands of Portuguese mobile communications providers, in order to discover the antecedents of customer-brand relationships and loyalty. A focus group and a web-based survey were conducted. Firstly, a qualitative method was used, in order to gain insight in the area. Later, a sample of 606 older Generation Y mobile communication users was employed. Optimus, TMN and Vodafone are all implementing marketing strategies based on emotions. They are building customer databases to manage relationships with their corporate brand/company, but our results reveal not all of them reach the same level of attitude towards their brand, reputation, tribalism or satisfaction with the brand. TMN, despite being the market leader, demonstrates a poor level of results in terms of customer-brand relationship building. Based on the findings of this research implications for marketing practice and directions for further research are discussed.